Life-years saved by advances in blood cancer therapy: a retrospective analysis - Dennis C Chang; Ann-Kathrin Eisfeld; Lee M Greenberger; E Anders Kolb (Blood Advances, 2026)
The impact of research and the development of therapeutics for blood cancer must be measured to direct future studies. Here, we used a life-years saved (LYS) methodology to quantify that impact. We estimate 25.8 million cumulative LYS across major blood cancer types in the US since 1949. The majority of LYS (~20 million) were for Hodgkin lymphoma (HL), acute lymphoblastic leukemia (ALL), and non-Hodgkin lymphoma (NHL). NHL stands out due to a high incidence, while HL and ALL have accumulated LYS over the longest period. LYS were lowest for acute myeloid leukemia and intermediate for multiple myeloma, chronic lymphocytic leukemia, and chronic myeloid leukemia. Progress has also been uneven across ages and racial groups. Black patients had worse survival outcomes than White patients for all blood cancers except multiple myeloma. The LYS methodology may be used to assess unmet needs and track progress, particularly where progress lags.